Effects of EPA and lipoic acid supplementation on circulating FGF21 and the fatty acid profile in overweight/obese women following a hypocaloric diet. Issue 5 (16th May 2018) - Escoté, Xavier; Félix-Soriano, Elisa; Gayoso, Lucía; Huerta, Ana Elsa; Alvarado, María Antonella; Ansorena, Diana; Astiasarán, Iciar; Martínez, J. Alfredo; Moreno-Aliaga, María Jesús
Abstract : EPA and LIP supplementation regulate the serum fatty acid profile. EPA supplementation also modulates the FGF21 level. Abstract : FGF21 has emerged as a key metabolism and energy homeostasis regulator. Dietary supplementation with eicosapentaenoic acid (EPA) and/or α-lipoic acid (LIP) has shown beneficial effects on obesity. In this study, we evaluated EPA and/or LIP effects on plasma FGF21 and the fatty acid (FA) profile in overweight/obese women following hypocaloric diets. At the baseline, FGF21 levels were negatively related to the AST/ALT ratio and HMW adiponectin. The weight loss did not cause any significant changes in FGF21 levels, but after the intervention FGF21 increased in EPA-supplemented groups compared to non-EPA-supplemented groups. EPA supplementation decreased the plasma n-6-PUFA content and increased n-3-PUFAs, mainly EPA and DPA, but not DHA. In the LIP-alone supplemented group a decrease in the total SFA and n-6-PUFA content was observed after the supplementation. Furthermore, EPA affected the desaturase activity, lowering Δ4D and raising Δ5/6D. These effects were not observed in the LIP-supplemented groups. Besides, the changes in FGF21 levels were associated with the changes in EPA, n-3-PUFAs, Δ5/6D, and n-6/n-3 PUFA ratio. Altogether, our study suggests that n-3-PUFAs influence FGF21 levels in obesity, although the specific mechanisms implicated remain to be elucidated.